Internationalisation and modernisation of processes in the higher education - Begimkulov, Uzokboy; Matnazarova, Mekhribon; Ismadiyarov, Yashin; Isyanova, Alfiya; Eshmamatov, Ismoil (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This article studies the aspects of the improvement in higher education in terms of advanced foreign experience. It deals with the organizational-methodical, contented aspects and the basic directions of modernization and implementation of modern curricula, and the programs of educational directions.